Investigation on Gender and Leadership in STEM in Higher Education: Methodology Design - Pereira, Leihge Roselle Rondon (2023)
Institutional actions and policies implemented by universities hold the potential to significantly impact the inclusion of women in leadership roles within STEM fields. This article describes the methodological design approved by the local ethics committee to conduct the research in Brazil, with the primary objective of understanding the degree to which discursive productions on gender affect women’s career experiences and leadership paths within STEM fields in higher education. Discursive productions include structures of power such as university policies, climate, culture, and projects. It is expected that the work will provide valuable insights and support for researchers sharing similar goals and who work to reduce gender inequalities in STEM.